Perancangan Media Informasi Berbasis Website Dengan Pendekatan Design thinking Untuk Penyebaran Konten Informasi dan Promosi Label Rekaman Musik Independen Warkop Musik - Resmadi, Idhar; Bastari, Rendy Pandita (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
The dissemination and promotion are very important for an independent music records label business. However, with the change in consumer behaviour, conventional ways of disseminating information through radio, television, or magazine/newspaper advertisements are no longer relevant and too much expensive. The use of social media and websites are potential efforts to be developed. But, the dissemination of information and promotion through social media are very limited to algorithms and technological capabilities. The importance of website could be very an effective medium for records label players. Website can create many varieties content informations and product campaigns. Moreover, with changes in consumer behaviour in consuming recorded music, there is a need for an ideal means of information and promotion to consumers. Through a design thinking approach, this design will focus on the needs of the end-user through the stages of empathy, define, ideation, prototype, and test. This series of processes are the stages that will be carried out in designing this website. Making this website can be an access to information and promotion for independent record labels, which so far have had various limitations. With the presence of this website, it is also expected to encourage information dissemination, access to promotions and marketing, as well as user data needs that can encourage the creation of various economic opportunities.